Safely and Actively Aging in Place: Older Adults’ Attitudes and Intentions Toward Smart Home Technologies - Tural, Elif (Gerontol Geriatr Med, 2021)
As smart technology use is growing in residential environments, research on how such technologies can provide opportunities for safely and actively aging in place by integrating physical activity into daily routines and reducing sedentariness is scarce. This study investigated older adults’ intentions to use and attitudes toward currently available smart home technologies that could contribute to safe and active lives in and around home. The focus was on four representative technologies: smart lighting, smart door locks, smart fire prevention devices, and smart home systems/home automation. This paper presents the results of a sequential mixed-methods study comprised of online and in-person surveys (n = 129), and a focus group of community-dwelling older adults, aged 50+ (n = 15). Ordinal regression analyses indicated that perceived usefulness consistently predicts older adults’ attitudes and willingness to use smart home products. While smart fire prevention devices were viewed most favorably due to their potential safety benefits, perceived affordability significantly influenced older adults’ intentions to use them in their homes. The focus group findings underscore technology skepticism, privacy concerns and return on investment as significant determinants of attitudes toward the smart design products. The study has implications of designers and manufacturers by providing insights on how to prioritize smart home technology integrations to homes.